Genomic landscape in Saudi patients with hepatocellular carcinoma using whole-genome sequencing: a pilot study - Hassanain, Mazen; Liu, Yang; Hussain, Weam; Binowayn, Albandri; Barakeh, Duna; Alsolme, Ebtehal; AlSaif, Faisal; Almasaad, Ghaida; AlSwayyed, Mohammed; Alaqel, Maram; Aljunidel, Rana; Abdelrahman, Sherin; et al. (Frontiers in Gastroenterology, 2023)
Background & Aims: Hepatocellular Carcinoma (HCC) is the third most prevalent cancer in Saudi Arabia. HCC poses a significant clinical challenge due to the presence of resistance among certain patients to the standard therapeutic agent, Sorafenib. Methods: Whole-genome sequencing (WGS) was performed on 16 HCC samples and targeted sequencing on 7 additional tumors. Employing the prize-collecting Steiner tree algorithm, we identified important altered genetic modules and potential biomarkers for each patient. Results: Out of the 13 patients who received sorafenib, three exhibited sensitivity, while the others showed resistance to the drug. Notably, 3 out of 16 individuals carried cancer-predisposing mutations. Additionally, 8 out of 16 patients displayed nonsynonymous somatic alterations in genes associated with cancer. In the targeted-sequencing samples, rare nonsynonymous variants were observed across all seven cases. The study also revealed the presence of specific somatic aberrations, including TP53, PIK3CA, APOB, CTNNB1, DPYD, LRP1B, MYC, and NFE2L2, which were identified in two patients. Among the 42 genes linked to sorafenib treatment, four out of ten resistant patients carried somatic nonsynonymous variants. Interestingly, none of the three Sorafenib-sensitive patients displayed any concerning variants in those genes. Conclusions: Our findings indicate that most of the HCC patients possess cancer-related genetic variants, and the altered pathways in these patients exhibit similarities. Notably, resistant patients exhibit a higher frequency of aberrations in sorafenib-related genes compared to sensitive patients. These results contribute to our understanding of the genetic landscape of HCC and highlight potential therapeutic targets that could aid in overcoming treatment resistance.